Guidelines for the management of cytomegalovirus infection in patients with haematological malignancies and after stem cell transplantation from the 2017 European Conference on Infections in Leukaemia (ECIL 7) - Ljungman, Per; de la Camara, Rafael; Robin, Christine; Crocchiolo, Roberto; Einsele, Hermann; Hill, Joshua A; Hubacek, Petr; Navarro, David; Cordonnier, Catherine; Ward, Katherine N; 2017 European Conference on Infections in Leukaemia group (The Lancet. Infectious diseases, 2019)
Cytomegalovirus is one of the most important infections to occur after allogeneic haematopoietic stem cell transplantation (HSCT), and an increasing number of reports indicate that cytomegalovirus is also a potentially important pathogen in patients treated with recently introduced drugs for hematological malignancies. Expert recommendations have been produced by the 2017 European Conference on Infections in Leukaemia (ECIL 7) after a review of the literature on the diagnosis and management of cytomegalovirus in patients after HSCT and in patients receiving other types of therapy for haematological malignancies. These recommendations cover diagnosis, preventive strategies such as prophylaxis and pre-emptive therapy, and management of cytomegalovirus disease. Antiviral drugs including maribavir and letermovir are in development and prospective clinical trials have recently been completed. However, management of patients with resistant or refractory cytomegalovirus infection or cytomegalovirus disease is a challenge. In this Review we summarise the reviewed literature and the recommendations of the ECIL 7 for management of cytomegalovirus in patients with haematological malignancies.
Keywords: Benzimidazoles; Antiviral Agents; Cytomegalovirus Infections; ganciklovir; antivirové látky; benzimidazoly; lidé; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; Cytomegalovirus; ribonukleosidy; Ganciclovir; směrnice pro lékařskou praxi jako téma; hematologické nádory; Hematologic Neoplasms; Ribonucleosides; Practice Guidelines as Topic; leukemie; cytomegalovirové infekce; Leukemia; Humans